Perilaku Politik Elite Muhammadiyah Pada PILKADA: Studi Kasus di Wilayah Kauman Temanggung Jawa Tengah - Andy Dermawan; Tulus Warsito; Mahli Zainuddin (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2019)
Abstract: This article seeks to explore the influential factors behind the high number of votes for the regent candidate promoted by Muhammadiyah Religious Organization through the National Mandate Party (PAN) in the Kauman Region of Temanggung Regency. Based on the theory of rational choice, this study reveals that the the Muhammadiyah elites in Temanggung in the 2013 Regional Election tended to apply moderate-accommodative political behavior. Muhammadiyah elites were inclined to take the middle path and took adaptive measurements to respond the emerging dynamics in the political realms of the regions. The community (respondents) opted to vote for Anif Punto as the regent candidate based on rational factors considering various indicators, such as the promises of the candidates and parties, the candidates’ capabilities, the candidate’s self-confidence in his performance, and the candidate’s and the party’s vision, mission and programs. Meanwhile, as seen from the perspective of maqasid asy-syari'ah theory, the elites and the Muhammadiyah citizens at large tended to apply freedom of choice in their political behavior and politicalawareness without restricted by ideological barriers, parties or community organizations they are engaged in. They opted to vote for candidates who, in their opinion, could provide them with better future assurance and at the same time provide greater benefit to the community. Abstrak: Artikel ini mengeksplorasi faktor-faktor yang mempengaruhi tingginya perolehan suara calon bupati yang diusung oleh Muhammadiyah melalui Partai Amanat Nasional (PAN) di wilayah Kauman Temanggung. Berdasar teori pilihan rasional, kajian ini menemukan fakta bahwa perilaku politik elite Muhammadiyah di Temanggung pada Pilkada 2013 adalah moderat-akomodatif. Elite Muhammadiyah memiliki kecenderungan mengambil jalan tengah dan beradaptasi dengan dinamika yang terjadi dalam realitas perpolitikan di daerah. Faktor-faktor yang mempengaruhi masyarakat (responden) memilih Anif Punto sebagai calon bupati adalah faktor rasional, yaitu mempertimbangkan berbagai indikator, seperti janji-janji calon dan partai, kemampuan calon, keyakinan terhadap kinerja calon, visi, misi, dan program calon dan partai. Sementara itu, jika dilihat dari perspektif maqashid asy-syari’ah, perilaku politik elite dan kesadaran warga Muhammadiyah dalam menentukan pilihannya tidak terbelenggu oleh sekat ideologi, partai atau organisasi masyarakat yang dinaungi. Pilihan ditujukan kepada calon yang menurut mereka bisa memberikan perlindungan yang lebih baik dan sekaligus memberikan kemanfaatan yang lebih besar kepada masyarakat.